Flypaper Effect on The Influence of General Allocation Funds and Original Regional Income on Regional Expenditure of North Sumatra Province - Hutagalung, Abdul Jalil; Sari, Raina Linda; Syafii, M. (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research analyzes the implementation of Vocational Education policies in Indonesia with a focus on the factors that influence the success of the program. Data was collected through surveys and interviews with various related parties, as well as reviewing official documents related to education policy. The research results highlight several important aspects, including the involvement of the industrial sector in the curriculum, the importance of adequate infrastructure, improving the quality of teachers, and synergy between educational institutions, government, and the industrial sector. These findings provide important insights into the strategic steps needed to increase the effectiveness and relevance of Vocational Education in preparing a workforce ready for global market demands. In conclusion, increasing collaboration and attention to these various aspects is the key to improving the quality and competitiveness of the Indonesian workforce in the future.